Sugarcane response to two biotic stressors: Diatraea saccharalis and Mahanarva fimbriolata - de Souza Rossato, J. A. [UNESP]; Fernandes, O. A. [UNESP]; Rossini Mutton, M. J. [UNESP]; Higley, L. G.; Madaleno, L. L. [UNESP] (Int Sugar Journal Ltd, 2011)
In a field experiment in 2007/08 in São Paulo state, Brazil cane was exposed to sugarcane borer (Diatraea saccharalis) and spittlebug (Mahanarva fimbriolata) alone or in combination. Plots comprised 2 m(2) caged and uncaged sugarcane stalks. Compared with the caged (un-infested) control, spittlebug nymphs decreased cane yield by 17.6%, whereas infestation from spittlebug nymphs + sugarcane borer combined and sugarcane borer alone, decreased cane yields by 15.5% and 6.9%, respectively. There was no significant difference among the treatments in levels of soluble solids and cane sucrose content.
Keywords: insect-plant relationship; Spittlebug; Sugarcane borer; Yield